interplay : Selected works from the Museum and private collections. - Boym, Per Bjarne; Stromodden, Jarle (Oslo : National Museum of Contemporary Art, 2000)
Barclay, Per ; Becher, Bernd & Hilla ; Blystad, Kristian ; Bourgeois, Louise ; Breivik, Bard ; Calle, Sophie ; Cragg, Tony (Anthony) ; Fridfinnsson, Hrein ; Fulton, Hamish ; Furunes, Anne Karin ; Förg, Gunther ; Gillick, Liam ; Goldin, Nan ; Gormley, Antony ; Herold, Georg ; Höfer, Candida ; Plenge Jakobsen, Henrik ; Brinch, Jes ; Jenssen, Olav Christopher ; Lasker, Jonathan ; McCarthy, Paul ; Ness, Ole Jorgen ; Samore, Sam ; Schütte, Thomas ; Serrano, Andres ; Sherman, Cindy ; Smith, Tony ; Struth, Thomas ; Sugimoto Hiroshi ; Taylor-Wood, Sam ; Tronvoll, Mette ; Woodman, Francesca ; Wool, Christopher
biog. per kunstenaar
Noors & Engels
Interplay : Selected works from the Museum and private collections, National Museum of Contemporary Art, Oslo, 17 June - 10 September 2000
boek